에너지 저장기술의 최적 서비스 선정 방법 - 이지현(Ji Hyun Lee); 제갈성(Seong Jegarl); 김현실(Hyunshil Kim); 맹종호(JongHo Maeng) (Current Photovoltaic Research, 2023)
The expanding significance of energy storage (ES) technology is increasing the acceptability of power systems by augmenting renewable energy supply. To deploy such ES technologies, we must select the optimal technology that meets the requirements of the system and confirm the technical and economic feasibility of the business model based on it. Herein, we propose a method and tool for selecting the optimal ES technology and service suitable for meeting the requirements of the system, based on its performance characteristics. The method described in this study can be used to discover and apply various ES technologies and develop business models with excellent economic feasibility.